THE ROLE OF INNOVATIVE TECHNOLOGIES IN INCREASING THE ECONOMIC EFFICIENCY OF RAILWAY TRANSPORT ENTERPRISES (Marketing Journal, 2025)
This article examines the role and significance of innovative technologies in enhancing the economic efficiency of railway transport enterprises. The impact of artificial intelligence, Internet of Things (IoT), digital twin technologies, and predictive maintenance systems on the performance of railway operations is analyzed. The findings indicate that implementing such technologies can reduce maintenance costs by up to 40%, increase infrastructure capacity by up to 40%, and significantly optimize energy con sumption.
Keywords: railway transport; innovative technologies; economic efficiency; artificial intelligence; IoT; digital transformation; predictive maintenance. № 1 70